พุทธปรัชญา : มิติการมองโลกและชีวิตตามความจริง - Singkumpong, Panuvat; Leeka, Jaras (Journal of Graduate MCU KhonKaen Campus, 2023)
This book review aims to present a Buddhist philosophy perspective on life and the real world. using principles, concepts, methods, processes and guidelines of Buddhism through a philosophical perspective in the form of a synthesis of Buddhist philosophy in the metaphysical, epistemological and ethical dimensions To create a set of knowledge in Buddhist philosophy to understand life and the real world. including the development of human potential at the level of ordinary people to the noble level and peaceful coexistence in society according to Buddhist philosophy